Understanding knowledge acquisitions through social media among university students - Badderudin, Puteri Alia Izzati (2019)
Universities students tend to own an account on several social media sites making the combination of social media within the learning environment to be simpler. The study focuses on the use of social media and how it facilitates knowledge acquisition. This study adopts qualitative study and conduct semi-structured interview to answer the research questions. Thematic analysis is used to analyze the data. Discussion of the findings is also provided through the use of educational learning theory as the theoretical lens to further understand student’s usage of social media. Besides, this study qualitative study successfully revealed findings and application of social media for knowledge acquisition among students based on educational learning theories such as behaviorism, cognitivism, constructivism, humanism, and connectivism. Although knowledge acquisition using social media is a complex phenomenon, it will definitely help researchers gain more insight into the topics by studying it in different settings and environment. This research contribute to higher learning institutions to identify the useful and powerful platform of social media for knowledge acquisition in helping students achieve better engagement in social media to acquire knowledge. Besides, it also provides an insight on the plausibility of “third variable explanation” for the results of the past studies along with contribution to theoretical development of social media in knowledge management especially in knowledge acquisition